Relationship between Prison Inmates level of Education and Crime Committed in Bauchi State - Yusuf, Aminu; Ningi, Garba Haruna; Adam, Muhammad; Sara, Safyanu Shu’aibu (Advances in Social Sciences Research Journal, 2018)
The study determined in percentages the relationship between prison inmate’s level of education and crime committed in terms of burglary, drug-related offences, rape, robbery and weapon-related offence cases in Bauchi State, Nigeria. A survey designed was used for the study. The population of the study consists of 761(male =753 and female= 8) prison inmates from the four (Azare, Bauchi, Ningi, and Jama’are) prison zones in the State. Proportionate stratified random sampling technique was used to select 247 prison inmates. Property/Violent Crime (PVC) structured interview was used as the instrument for data collection. To ensure the reliability of the information coded from the interviewed, the information collected was subjected to further verification from the prison record officer in each of the 4 zone. Hypotheses were tested at α = 0.05 level significance. 98% of the prison inmate that commit burglary case had no post-secondary school certificate; 90% of the prison inmates that commits robbery case were either illiterate or had qualification below undergraduate certificate and there is a significant (Chi-square = 32.231, p < 0.05) relationship between prison inmate level of education on robbery and weapons-related offences cases, were among the findings from the study. Recommendation made includes the provision of free and compulsory post-secondary school education by the State government and similar study to be carried out in other states of Nigeria to verify some of the findings from the study.